PERAN PENILAIAN FORMATIF DALAM MENINGKATKAN PEMAHAMAN SEJARAH KEBUDAYAAN ISLAM - Anya Dani Kinasih; Noorazamah Hidayati (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
Education plays a crucial role in shaping the character and understanding of students. Students, especially through the subject of Islamic Culture History (SKI) which teaches the history and moral and spiritual values of Islam. Teaching history as well as Islamic moral and spiritual values. Learning SKI learning faces the challenge of delivering complex material, this formative assessment is seen as a strategic evaluation method to improve student understanding. Formative assessment allows teachers to monitor student progress and provide constructive feedback, which plays an important role in improving the quality of learning. Plays an important role in improving the quality of learning. The use of technology, such as the Quizizz app, in formative assessment offers an interactive approach that can increase student motivation and student engagement. The app provides real-time feedback, so students can identify areas of improvement directly. Although effective in interactive learning, the use of technology such as Quizizz has its own drawbacks, such as dependence on technological devices and limitations in in-depth assessment. In-depth assessment. Therefore, teachers need to combine this technology with other methods to make the SKI learning process more effective and inclusive. This article examines the role, advantages and challenges of technology-based formative assessment in SKI learning. Challenges of technology-based formative assessment in SKI learning, which is expected to help educators optimally implement this method optimally to improve students' understanding.